2018
DOI: 10.1007/s10545-018-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for homocystinurias: recent recommendations versus current practice

Abstract: Due to the favourable outcome of early treated patients, NBS for homocystinurias is recommended. To improve NBS, decision limits should be revised considering the population median. Relevant markers should be combined; use of the postanalytical tools offered by the CLIR project (Collaborative Laboratory Integrated Reports, which considers, e.g. birth weight and gestational age) is recommended. tHcy and methylmalonic acid should be implemented as second-tier markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…A relevant finding of our study was the observation that the four children identified by NBS were the only ones with a DQ within normal range, with a normal brain MRI and lacking epilepsy. This supports previous studies suggesting that an early diagnosis using NBS can allow a better outcome, as it reduces the exposition to offending metabolites and prevents the occurrence of major disease‐related events (eg, hydrocephalus, hemolytic uremic syndrome, pulmonary hypertension) that greatly contribute to long‐term disabilities in cblC defect. It is of interest that children with symptomatic diagnosis in the neonatal age, who had a relatively short exposure to toxic metabolites, still had a lower level of development in all examined abilities when compared to those identified by NBS.…”
Section: Discussionsupporting
confidence: 90%
“…A relevant finding of our study was the observation that the four children identified by NBS were the only ones with a DQ within normal range, with a normal brain MRI and lacking epilepsy. This supports previous studies suggesting that an early diagnosis using NBS can allow a better outcome, as it reduces the exposition to offending metabolites and prevents the occurrence of major disease‐related events (eg, hydrocephalus, hemolytic uremic syndrome, pulmonary hypertension) that greatly contribute to long‐term disabilities in cblC defect. It is of interest that children with symptomatic diagnosis in the neonatal age, who had a relatively short exposure to toxic metabolites, still had a lower level of development in all examined abilities when compared to those identified by NBS.…”
Section: Discussionsupporting
confidence: 90%
“…It is known that patients with milder forms of inborn errors of Cbl metabolism have been missed by similar screening approaches and so most likely, not all clinically relevant cases of maternal Cbl deficiency in the neonate will be detectable using this algorithm. The post‐analytical tools offered by the Collaborative Laboratory Integrated Reports project seem promising for a general improvement of newborn screening for remethylation disorders.…”
Section: Acquired Cbl Deficienciesmentioning
confidence: 99%
“…Gramer et al proposed second tier Hcy measurement in dried blood spots when first tier testing is abnormal and concluded that neonates with severe Cbl deprivation can be detected without causing unreasonable costs or recall rates 11 . It is known that patients with milder forms of inborn errors of Cbl metabolism have been missed by similar screening approaches 30 and so most likely, not all clinically relevant cases of maternal Cbl deficiency in the neonate will be detectable using this algorithm. The post-analytical tools offered by the Collaborative Laboratory Integrated Reports project seem promising for a general improvement of newborn screening for remethylation disorders 30,31 .…”
Section: Acquired Cbl Deficiencies: Background and Clinical Presentmentioning
confidence: 99%
See 2 more Smart Citations